Baseline neutrophil-lymphocyte ratio is associated with outcomes in patients with castration-resistant prostate cancer treated with Docetaxel in South China. Issue 39 (1st October 2021) - Jiang, Zhi-guo; Liao, Shao-Guang
Abstract : Abstract: The aim of this study is to investigate the association between baseline neutrophil-to-lymphocyte ratio (NLR) and progression-free survival (PFS), overall survival (OS) and radiological response in castration-resistant prostate cancer patients treated with docetaxel. Forty-one prostate cancer patients who were treated with docetaxel were selected. Univariable and multivariable Cox regression models were used to predict the association of baseline NLR as a dichotomous variable with PFS and OS after chemotherapy initiation. In Kaplan–Meier analysis, the median PFS (9.8 vs 7.5 months, P = .039, Fig. 1 ) and OS (17.6 vs 14.2 months, P  = .021, Fig. 2 ) was higher in patients who did not have an elevated NLR than in those with an elevated NLR. In univariate analysis, the pretreatment NLR was significantly associated with PFS ( P  = .049) and OS ( P  = .023). In multivariable analysis, patients with a NLR of >3 were at significantly higher risk of tumor progress (hazard ratio 2.458; 95% confidence interval 1.186–5.093; P  = .016) and death (hazard ratio 3.435; 95% CI 1.522–7.750; P  = .003)than patients with a NLR of ⩽3. NLR may be an independent predictor of PFS and OS in castration-resistant prostate cancer patients treated with docetaxel. The findings require validation in further prospective, big sample-sized studies.